(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Language is in constant flux, shaped by societal shifts, technological advancements, and cultural interactions. Dictionaries play a crucial role in documenting and sometimes influencing these changes. This paper explores how dictionaries capture language evolution, from recording new words and meanings to retiring obsolete terms. By examining the lexicographical processes behind dictionary creation and updates, this study highlights dictionaries as essential tools for understanding linguistic shifts, preserving language history, and guiding language use. Through an analysis of contemporary and historical dictionaries, this article underscores the importance of lexicography in reflecting and guiding language development.